Spatial and Temporal Distribution of Soil Microbial Properties in Two Shrub Intercrop Systems of the Sahel - Diedhiou-Sall, Sire; Assigbetsee, Komi B.; Badiane, Aminata N.; Diedhiou, Ibrahima; Khouma, M.; Dick, Richard P. (Frontiers in Sustainable Food Systems, 2021)
The Sahel is an ecologically vulnerable region where increasing populations with a concurrent increase in agricultural intensity has degraded soils. Agroforestry offers an approach to remediate these landscapes. A largely unrecognized agroforestry resource in the Sahel are the native shrubs, Piliostigma reticulatum, and Guiera senegalensis that to varying degrees already coexist with row crops. These shrubs improve soil quality, redistribute water from the deep soil to the surface (hydraulic lift), and can improve crop growth. However, little information is available on whether these shrubs affect spatial and temporal dynamics of microbial communities. Therefore, the objective of this study was to determine microbial composition and activity in the wet and dry seasons of soil in the: shrub rhizosphere (RhizS), inter-root zone (IntrS), and outside the influence of shrub soil (OutS) for both G. senegalensis and P. reticulatum in Senegal. A 3 × 2 factorial field experiment was imposed at two locations (490 and 700 mm annual rainfall with G. senegalensis and P. reticulatum, respectively), that had the soil sampling treatments of three locations (RhizS, IntrS, and OutS) and two seasons (wet and dry). Soils were analyzed for: microbial diversity (DGGE with bacterial 16S or fungal 28S rRNA gene sequences phospholipids fatty acid, PLFA); enzyme activities; microbial biomass carbon (MBC); and nitrogen (N) mineralization potential. For the DGGE profiling, the bacterial community responded more to the rhizosphere effect, whereas, the fungal community was more sensitive to season. PLFA, MBC, enzyme activities and inorganic N were significantly higher in both seasons for the RhizS. The presence of shrubs maintained rhizosphere microbial communities and activity during the dry season. This represents a paradigm shift for semi-arid environments where logically it would be expected to have no microbial activity in the extended dry season. In contrast this study has shown this is not the case that rather the presence of shrub roots maintained the microbial community in the dry season most likely due to hydraulic lift and root exudates. This has implications when these shrubs are in cropped fields in that decomposition and mineralization of nutrients can proceed in the dry season. Thus, enabling accumulation of plant available nutrients during the dry season for uptake by crops in the rainy season.